The "Corona Warriors"? Community health workers in the governance of India's COVID-19 response. (November 2022) - Nichols, Carly; Jalali, Falak; Fischer, Harry
Abstract: India's nearly 1-million strong band of quasi-volunteer accredited social health activists (ASHAs) have been key actors in government efforts to control COVID-19. Utilizing a nationalist rhetoric of war, ASHAs were swiftly mobilized by the government in March 2020 as 'COVID warriors' engaged in tracking illness, disseminating information, and caring for quarantined individuals. The speed at which ASHAs were mobilized into mentally and physically grueling labor was all the more stunning given these minimally paid community health workers have long been seen to have low morale given their precarious, informalized work arrangements. Building on work examining the spatialities of global health governance alongside literature on geographic contingency, this paper explores the ways that nationalist COVID-19 war rhetoric promulgated from Delhi worked as a technology of health governance to propel ASHAs into certain forms of action, yet also opened up spaces of potentiality for them to reimagine their relationship to both the state and the communities they serve. In particular, in our analysis of in-depth telephone interviews with ASHA workers in the state of Himachal Pradesh, we find that their hailing as COVID warriors inspired patriotic calls to duty and legitimized their (long over-looked) roles as critical governance actors, yet also was subject to resistance and reworking due to a combination of institutional histories, local politics, as well as happenstantial everyday encounters of ASHA work. The precarious employment of ASHAs – in terms of basic remuneration as well as the great on-the-job risks that they have faced – underscores both the fragile nature of India's health governance system as well as possible political movements for its renewal. We conclude by calling for geographers to give greater attention to community health care workers as a key window into understanding the uneven ways in which health systems are made manifest on the ground, and their ability to respond to citizens' healthcare needs – both in the COVID-19 pandemic and beyond.